Pengembangan Media Papan Jurang (Penjumlahan dan Pengurangan) dalam Meningkatkan Kemampuan Berhitung Siswa Kelas I di SDN 2 Kalijaga - Zahrotul Hayati; Ahmad Sulhan; Djuita Hidayati (Mataram University, 2026)
This research is motivated by the lack of numeracy skills in grade 1 students and the lack of use of learning media that can help students in learning mathematics, and in this study the researcher used the gap board media (addition and subtraction) in improving students' numeracy skills. Therefore, this study aims to determine the feasibility, practicality and effectiveness of the gap board media (addition and subtraction) in improving the numeracy skills of grade 1 elementary school students. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study subjects consisted of media expert validators, material experts, and 23 first-grade students (10 girls and 13 boys). Data were collected through questionnaires, tests, interviews, and observations, then analyzed using qualitative and quantitative techniques. The results showed that the